Sinapine improves LPS-induced oxidative stress in hepatocytes by down-regulating MCJ protein expression - Li, Youdong; Xu, Yong-Jiang; Tan, Chin Ping; Liu, Yuanfa (Elsevier, 2022)
Oxidative stress is an important part of the development of NAFLD, and hepatic injury can be prevented by inhibiting oxidative stress. In this study, we investigated the potential role of sinapine in protecting the liver. LPS was selected to establish the oxidative stress model of THLE-2 cells, and the treatment concentrations of LPS (5 μg/mL) and sinapine (5 μM, 20 μM, and 80 μM) were determined by toxicity experiments. The MDA of the sinapine (80 μM) pretreatment group was 1.09 ± 0.13 nmol/mg prot which was reduced by 27.67 % compared with the LPS group. Furthermore, SOD and GSH-Px levels were significantly increased by 40.61 % and 49.60 %, respectively. And the ROS levels of 20 and 80 μM sinapine were reduced by 31.47 % and 40.31 %, respectively (p < 0.01) compared with the model group. The mitochondrial membrane potential had similar results. It was also found that sinapine can significantly down-regulate the level of MCJ protein (p < 0.01), which is related to oxidative stress. Our results indicate that sinapine can maintain liver health by down-regulating the expression of MCJ protein to inhibit oxidative stress, which provides a theoretical basis for the use of sinapine as an inhibitor of MCJ.